ESTIMASI NILAI CADANGAN KARBON MENGGUNAKAN ANALISIS NDVI (NORMALIZED DIFFERENCE VEGETATION INDEX) DI KHDTK UNIVERSITAS LAMBUNG MANGKURAT - Dea Karmila; Ahmad Jauhari; Rina Kanti (Jurnal Sylva Scienteae, 2020)
This research aims to determine the value of carbon stock based on the NDVI and make a connection between the value of NDVI and the value of carbon stock. This research was conducted at KHDTK Lambung Mangkurat University, South Borneo. The time needed to carry out this research for four months, from january to April, which includes research preparation, data collection and preparation of research reports.  Estimation of carbon stock calculated from 47% of biomass value with trees >10 cm in diameter on three types of vegetation density. Vegetation density was predicted using the NDVI value processed using QGIS software and based on field observations. The value of NDVI at very rare densities  with the range of value (0.52-0.59),at rare densities with the range of value (0.69-0.77), and at medium densities with the range of value (0.81-0.85). The value of carbon stock in three types of vegetation density each are 3.34 (ton/ha) at very rare densities, 11.61 (ton/ha) at rare densities to medium, and 32.04 (ton/ha) at medium densities. The relationship between the value of NDVI and the value of carbon stock uses the exponential regression equation model y = 0.0304e8.2416x and determination coefficient R2=0.909. determination coefficient R2>0.40 show strong relationships, thus the greater the value of R2 between NDVI and stock carbon are better.